Developing English Proficiency through Qualitative Study of “English With Lucy” YouTube Channel - Simbolon, Sulistina Ratulani; Ismahani, Siti (The Journal of Educational Development, 2024)
In the era of globalization, utilizing online platforms for language learning has become increasingly prevalent. This study explores the use of the YouTube channel "English with Lucy" as a learning medium to enhance high school students' English speaking skills. The research aims to investigate the effectiveness of the "English with Lucy" YouTube channel in improving students' vocabulary, pronunciation, and grammar usage. Employing a qualitative descriptive approach, this study conducted observations and in-depth interviews with 26 high school students who actively engaged with the channel's content over a period of six weeks. The results revealed that 19 students displayed significant progress in vocabulary acquisition and pronunciation skills, while 7 students showed moderate improvement. Additionally, students appreciated the interactive elements and diverse content provided by the channel, which facilitated their learning process. The study concludes that the "English with Lucy" YouTube channel is an effective tool for developing English speaking skills among high school students. The findings highlight the potential of online educational resources in enhancing language proficiency and underscore the importance of integrating digital platforms into traditional educational practices.